Developing Students’ Lexical Competence in A Foreign Language Through The “Concept Analysis” Method - Sadinov Oybek (International Journal Of Literature And Languages, 2026)
The development of lexical competence remains one of the central problems of foreign language education because vocabulary knowledge directly conditions comprehension, oral interaction, written production, and the precision of meaning-making. In contemporary language pedagogy, lexical competence is no longer interpreted as the mere accumulation of isolated words; rather, it is understood as the ability to select, relate, control, and use vocabulary in context. This article examines the didactic potential of the “concept analysis” method for developing students’ lexical competence in a foreign language. In this study, the concept analysis method is treated as an umbrella instructional approach that includes concept mapping, semantic mapping, and semantic feature analysis, since these techniques organize lexical units through category, feature, hierarchy, and semantic relations. The article based on an integrative review of official Council of Europe documents and peer-reviewed studies published between 2001 and 2025. The analysis shows that concept-oriented vocabulary work strengthens both the breadth and the depth of lexical knowledge, improves retention, supports transfer from receptive to productive use, and promotes more accurate lexical choice in speech and writing. At the same time, the effectiveness of the method depends on careful task design, sufficient duration, and the integration of conceptual work with communicative practice. The article argues that the concept analysis method should be viewed not as an auxiliary graphic activity, but as a didactic mechanism for restructuring lexical knowledge and transforming vocabulary learning from memorization into meaningful conceptual development.